Analisis Bibliometrik Perkembangan Penelitian Preservasi Pengetahuan Di Indonesia - Nurhayati, Euis Sri; Salim, Tamara Adriani (Universitas Islam Negeri Sumatera Utara, 2023)
This research examines the development of research trends regarding knowledge preservation in Indonesia. The research aims to determine: (1) the development of the number of international publications regarding knowledge preservation in Indonesia in the Scopus database in 2012–2022, (2) the core journal, (3) the contribution of research institutions, (4) researcher productivity, (5) a development map based on subjects or fields, (6) keywords (co-words), and (7) authors (co-authors). Data collection was carried out using the keywords